Corporate environmental ethics as a catalyst: Strengthening green innovation for sustainable competitive advantage - Magda Siahaan; Edi Sopyan; Theonino David N; Hofandrik Lase (Politeknik Ganesha Medan, 2026)
This study empirically evaluates the influence of green intellectual capital, green innovation, and environmental management on green competitive advantage, with corporate environmental ethics as a moderating variable. The associative hypothesis-testing method was used on primary data from a survey, distributing questionnaires to all employees of 238 industrial companies and 30 industrial companies in Indonesia, using purposive sampling, and the data were analyzed using the SEM method in AMOS software. Achieving Green competitive advantage through environmentally conscious human resources, strong corporate ethics, green structural and relational capital management, and sustainable organizational culture, although integrated implementation, is still a challenge in Indonesia. This research implication Incorporates environmental ethics, cultivates sustainable human resources, executes sustainability strategies, and emphasises the triple bottom line to attain a green competitive advantage; furthermore, the government can facilitate this through incentives, regulations, and the promotion of environmental awareness.